The Effect Of Using Ted Talks Application On The Listening Skills Mastery Of Second Semester Students In The English Education Study Program - Celine Anggreani Napitupulu; Febrika Dwi Febrika; Srisofian Sianturi (STABN RADEN WIJAYA WONOGIRI, 2020)
This study investigates the effect of using the TED Talks application on the listening skills mastery of second-semester students in the English Education Study Program at the University of HKBP Nommensen. TED Talks, as an authentic multimedia platform, provides learners with real-life English exposure through engaging videos covering diverse topics. A quantitative experimental method was employed, involving two groups: Class B as the experimental group and Class A as the control group. The experimental group, consisting of 25 students, was taught using TED Talks, while the control group of 31 students received instruction through conventional methods. Both groups took a pre-test and a post-test to measure the development of their listening skills. The findings revealed a significant improvement in the experimental group’s average score, increasing from 59.6 to 70,24, compared to the control group’s rise from 57.16 to 64.38. The t-test analysis produced a t-observed value of 2.571, which exceeded the t-table value of 2.005 at a 0.05 significance level, indicating a statistically significant difference. These results support the alternative hypothesis (Ha) and demonstrate that the use of TED Talks positively impacts students’ listening skills. Therefore, TED Talks can be considered an effective and innovative tool for enhancing listening instruction in EFL university settings